The ecology of risk in an informal settlement: interpersonal conflict, social networks, and household food security - Gilbertson, A; Adam Gilbertson (2013)
Kenyan informal settlements have been thoroughly depicted by previous researchers as biophysical, epidemiological, and economic risk environments in which food insecurity is recognised as one of the most persistent everyday challenges. Although unemployment and illness are key contributors to the inability to purchase sufficient food, the reasons why households experience food insecurity are more complicated and not fully understood. Part of the problem is that few previous studies have privileged socio-political contributions (e.g. gender-based power inequalities and the impacts of social networks) to household food security risk. Whilst food security researchers commonly utilise the concept of vulnerability to address household-scale risk, this concept is rarely applied to interpersonal dynamics within households. Using data gathered through participant observation, questionnaires, and 109 in-depth interviews with 67 participants, this thesis provides an ethnographic account of household food insecurity in an informal settlement which addresses three primary questions: (1) In what ways might interpersonal relationships within households contribute social and political obstacles to achieving food security? For instance, how and why might risk for food insecurity emerge from experiences of interpersonal conflict? (2) What role do extra-household social networks play in experiences of food security within households? (3) How useful is the concept of vulnerability for addressing experiences of risk which are negotiated between household members? In the informal settlement of 'Bangladesh', Mombasa, Kenya, conflict within domestic, especially conjugal, relationships represents a potential source of risk to food security for individual members or entire households. Contributing to this conflict are gender inequality, power differentials, the failure to meet marital expectations, and how people respond when presente with risk. Resulting experiences of food insecurity are shown to contribute to further conflict in the household, thereby creating a cycle of conflict and food insecurity. Those who find that they have insufficient food at home may receive assistance (food or money) from members of their social networks. However, these relationships may also contribute to experiences of conflict, and therefore insecurity, within households. Applying concepts of vulnerabilty to account for experiences of risk and their consequences (food insecurity) requires differentiating between what represents a hazard, a response, and an outcome. Within multi-person households, it is exceedingly difficult to divide lived experiences involving interpersonal conflict among these three categories. Thus, I argue that vulnerability is less useful for research concerning intra-household dynamics than it is for studies which assume households to be undifferentiated units.